Organizational Restructuring and Work Engagement Effects on Employee Performance: The Mediating Role of Job Satisfaction - Eko Darmo; Nurul Hermina (Al-Qalam Institue, 2026)
This study aims to analyze the effects of organizational restructuring and work engagement on employee performance, with job satisfaction as a mediating variable. This research uses a quantitative approach, employing descriptive and verificatory methods through a survey. The population consists of all employees in the Sales Division affected by organizational restructuring, and a saturated sampling technique was applied. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that organizational restructuring, work engagement, job satisfaction, and employee performance are generally in the very high category. Hypothesis testing reveals that organizational restructuring does not have a direct significant effect on employee performance. In contrast, work engagement has a positive and significant effect on employee performance. Furthermore, organizational restructuring and work engagement have a positive and significant effect on job satisfaction, and job satisfaction significantly influences employee performance. Mediation analysis confirms that job satisfaction mediates the relationship between organizational restructuring and employee performance, as well as between work engagement and employee performance. These findings indicate that improving employee performance requires not only structural changes but also efforts to enhance work engagement and job satisfaction to achieve sustainable performance outcomes.